2020
DOI: 10.21873/anticanres.14469
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Suppresses Proliferation of Liver Cancer Cell Lines In Vitro

Abstract: Background/Aim: We investigated the antiproliferative effect of quercetin on liver cancer cell lines. Materials and Methods: Thirteen liver cancer cell lines were cultured followed by treatment with varying concentrations of quercetin (0-100 μM) or quercetin and 5-FU, and the cell viability was analysed by the MTT assay. Flow cytometry was also used to examine cell cycle progression after treatment with quercetin. Results: The addition of quercetin resulted in a dose-and time-dependent suppression of cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…Hepatocellular carcinoma Qu prevents the liver cancerous cells proliferation through initiation of apoptosis and cell cycle arrest. [151] Colon cancer Induction of apoptosis was noticed in colon cancer through the Qu treatment. [152] Renal cancer Qu mitigates the adverse impact of sunitinib (a primary renal cancer treating drug); Qu-3-O-β-D-glucopyranoside was observed-that is, iso-Qu has an enhanced pharmacokinetic report.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma Qu prevents the liver cancerous cells proliferation through initiation of apoptosis and cell cycle arrest. [151] Colon cancer Induction of apoptosis was noticed in colon cancer through the Qu treatment. [152] Renal cancer Qu mitigates the adverse impact of sunitinib (a primary renal cancer treating drug); Qu-3-O-β-D-glucopyranoside was observed-that is, iso-Qu has an enhanced pharmacokinetic report.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Another in vitro study, conducted by Hisaka et al, stated that Qu prevents the liver cancerous cell proliferation through initiation of apoptosis and cell cycle arrest. Liver cell lines were treated with different dosages of varying concentrations of Qu, and cell viability along with cell cycle progression, were assessed, which concluded that treatment with Qu and 5-Fuorouracil caused a synergetic effect, and most cell lines showed cell cycle arrest at different cell cycle stages [151]. Qu regulates other related signaling pathways via initiation of the phosphorylation of Sp-1, Src-1, and STAT5, which are responsible for the progression of cancer [228].…”
Section: Liver Cancermentioning
confidence: 99%
“…Quercetin showed remarkable inhibitory effects on malignant cells like breast, lung, gastric, ovarian, colorectal and hepatic cancers [ 11 ]. Anticancer effects of quercetin were reported due to several mechanisms like cell apoptosis, inhibition of angiogenesis, inhibiting P-gp channel, decreasing oncogene expression and regulating specific signaling pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been demonstrated that quercetin suppressed hepatocellular carcinoma (HCC) cell proliferation in a concentration-and timedependent manner as well as induced cell-cycle arrest at different phases, in relation to the cell line employed. Among the 13 HCC cell lines tested, quercetin blocked cell cycle in G0/G1, S or G2/M phases in 4, 2 and 6 lines, respectively [10]. In HepG2 cell lines, quercetin reduced cell proliferation along with lowering the expression of the checkpoint kinase-1 (CHEK1), leading to the downstream regulation of both cyclins A and E and hence the cell-cycle blockage [11].…”
Section: Induction Of Anti-proliferative Effectsmentioning
confidence: 99%